Design of the Internal Personnel Administration Information System at the Regional Personnel and Human Resource Development Agency of Jambi City - Feri Pebrianto; Renaldi Yulvianda; Mochammad Arief Hermawan Sutoyo (MASE - Media Applied and Engineering, 2025)
The city of Jambi is an administrative entity responsible for assisting the mayor in matters related to staffing, education, and training. Currently, the administrative process, particularly in task letter numbering, still encounters issues with number duplication. Therefore, an internal administrative information system using PHP programming language and MySQL DBMS is needed. The system development method used is the waterfall model with a unified model language approach, utilizing activity diagrams, use case diagrams, and class diagrams. This information system produces outputs that display the accumulated days of official trips per employee and generates task letters as well as travel orders automatically according to the official document format, thereby facilitating the printing and reporting process at the Regional Personnel and Human Resources Development Agency of Jambi City.